The Impact of Education and Training, and Self-Efficacy on Employee Performance with Work Ability as an Intervening Variable - Tandipayuk, Maryanti; Zakaria, Zakaria; Mulyanti, Rita Yuni (Jurnal Manajemen Bisnis, 2024)
This study examines the impact of education training and self-efficacy on employee performance at the Directorate General of Sea Transportation Office in Merauke. The research aims to determine how these factors influence work ability and employee performance. Using a quantitative approach, the findings reveal that education, training, and self-efficacy positively and significantly affect work ability and employee performance. Additionally, work ability mediates these relationships. The study implies that organizations should invest in structured training programs and self-efficacy development to enhance employee performance. Further research should consider other factors that influence job motivation and work environment.